A vocabulary of thinking : Gertrude Stein and contemporary North American women's innovative writing - Mix, Deborah M. (University Of Iowa Press, 2007)
Using experimental style as a framework for close readings of writings produced by late twentieth-century North American women, Deborah Mix places Gertrude Stein at the center of a feminist and multicultural account of twentieth-century innovative writing. Her meticulously argued work maps literary affiliations that connect Stein to the work of Harryette Mullen, Daphne Marlatt, Betsy Warland, Lyn Hejinian, and Theresa Hak Kyung Cha.